Vegetation diversity and air pollution mitigation in urban green areas - Raisa Widya Putri; Dwi Nowo Martono; Sri Setiawati Tumuyu (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Fine particulate matter (PM₂.₅) pollution is a major environmental and public health concern in Jakarta. Urban green open spaces may contribute to air pollution mitigation through vegetation characteristics. This study aimed to examine the association between vegetation diversity and annual mean ambient PM₂.₅ concentrations in two urban green spaces in Jakarta. Methods: A quantitative and spatial analysis was conducted using vegetation plot data, Sentinel-2A imagery, and secondary air-quality data. Vegetation structure and diversity were analyzed using the Importance Value Index and Shannon–Wiener diversity index. Spatial vegetation distribution was analyzed using QGIS 3.34.4 and Sentinel-2A. Findings: Tebet Eco Park had a higher tree-species diversity index (H’ = 2.32) than integrated child-friendly public space/ruang publik terpadu ramah anak (RPTRA) Kelapa Nias III (H’ = 1.52). The corresponding annual mean ambient PM₂.₅ concentrations were 28 µg/m³ for the area associated with Tebet Eco Park and 31.9 µg/m³ for the area associated with RPTRA Kelapa Nias III. The lower PM₂.₅ value observed in the Tebet Eco Park area coincided with greater tree diversity and denser vegetation cover. However, because the PM₂.₅ data were obtained from secondary regional monitoring and the study did not directly measure traffic intensity, meteorological conditions, local emission sources, or pedestrian-level exposure, the findings should be interpreted as an observed association rather than evidence of a direct causal effect of vegetation. Conclusion: Tree-species diversity and vegetation structure may support the air-quality and public health functions of urban green spaces. Urban green-space management should prioritize species diversification, multilayered vegetation, shrubs and hedges near pedestrian areas, and the integration of vegetation planning with site-level air-quality, traffic, and meteorological monitoring. Novelty/Originality of this article: This study provides a public health-oriented comparison of two urban green spaces by integrating field-based vegetation diversity and structure, satellite-derived vegetation density, and annual PM₂.₅ data, thereby offering context-specific evidence for vegetation-quality-based urban greening in Jakarta.